2017
DOI: 10.11005/jbm.2017.24.2.97
|View full text |Cite
|
Sign up to set email alerts
|

Paget's Disease: Skeletal Manifestations and Effect of Bisphosphonates

Abstract: BackgroundPaget's disease of bone leads to change in the shape and size of the bone and results in reduced bone strength, leading to the complications of deformity, arthritis, and fracture. Due to unknown reasons, Paget's disease is rare in Asian descendants. We report the cases of Paget's disease who visited our institute for 15 years and reviewed the literatures.MethodsWe retrospectively reviewed the medical records and radiograms of 8 patients (6 female and 2 male) who were diagnosed as Paget's disease of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 17 publications
0
7
0
2
Order By: Relevance
“…In PDB, excessive over-activity of osteoblasts and osteoclasts might also result in the deposition of low-quality woven bone or area of osteolysis, resulting in deformity, secondary osteoarthritis and fracture. [ 20 ] It is presumed that stress fracture might occur in patients with PDB. [ 20 , 21 ] Although the exact etiology remains unclear, there are few possible explanations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In PDB, excessive over-activity of osteoblasts and osteoclasts might also result in the deposition of low-quality woven bone or area of osteolysis, resulting in deformity, secondary osteoarthritis and fracture. [ 20 ] It is presumed that stress fracture might occur in patients with PDB. [ 20 , 21 ] Although the exact etiology remains unclear, there are few possible explanations.…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 ] It is presumed that stress fracture might occur in patients with PDB. [ 20 , 21 ] Although the exact etiology remains unclear, there are few possible explanations. First, bisphosphonate is a strong precipitating factor that is associated with a stress fracture.…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] In fact, only a few cases of PDB have been reported, and to date, no epidemiological studies have been reported in the Republic of Korea. [6][7][8] A positive family history is observed in approximately 15% to 30% of patients, and first-degree relatives of patients with PDB show an approximately 7-fold higher risk of PDB. Familial PDB is diagnosed in younger individuals and affects more multiple bony involvement than sporadic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical findings range from an incidental radiological abnormality of “sclerotic-lytic” pattern of bones and an asymptomatic elevation of alkaline phosphatase to significant musculoskeletal symptoms such as bone pains, pathological fractures, macrocephaly, bony deformities, secondary osteoarthritis, compressive symptoms in the form of hearing and visual loss, vascular steal syndromes, a high-output heart failure, and osteosarcoma in <1% of affected patients. [ 7 ] A high index of suspicion is often needed to identify these clinical findings to make a diagnosis of Paget's disease. Treatment is indicated in symptomatic cases and in certain asymptomatic patients where biochemical parameters and radiological features indicate risk from untreated disease.…”
mentioning
confidence: 99%